Soluble Thrombomodulin Antigen in Conditioned Medium Is Increased by Damage of Endothelial Cells - Ishii, Hidemi; Uchiyama, Hiroyuki; Kazama, Mutsuyoshi (Thrombosis and Haemostasis, 1991)
Thrombomodulin (TM) exists not only in endothelial cells but also in circulating plasma as soluble heterogeneous fragments. A release mechanism of soluble TM antigen from endothelial cells was investigated. Cultured human umbilical vein endothelial cells released about 0.6% of total cellular TM antigen into conditioned medium during 24 h. The release of TM antigen was not influenced by addition of various concentrations (0.01-5.0 μM) of monensin, which inhibits intracellular transport of secretory proteins, though the secretion of plasminogen activator inhibitor-1 from the cells was inhibited. The release of TM antigen was not increased when total cellular TM level increased 1.3- or 1.4-fold relative to control cells after stimulation with 0.1-1.0 U/ml thrombin or 3 mM dibutyryl cAMP, respectively. Exposure of endothelial cells for 6 h to mixture of 1 μM N-formyl-methionyl-leucyl-phenylalanine (FMLP) and 100 ng/ml lipopolysaccharide (LPS) decreased cellular TM level by 30% relative to control cells without increase in the TM release. The FMLP and LPS-stimulated leukocyte treatment of the cells increased the release of TM antigens into the medium in a time-dependent manner and the increased release of TM antigen paralleled the extent of cell damage as measured by 51Cr release. Hydrogen peroxide treatment of the cells increased the release of TM antigens into the medium in a time- and concentration-dependent manner. The increased release of TM antigen by hydrogen peroxide also paralleled the extent of cell damage. Soluble TM antigen in conditioned medium from the untreated control cells was composed of six heterogeneous fragments of 105, 56, 48, 33, 31 and 28 kDa observed on Western blots after sodium dodecyl sulfatepolyacrylamide gel electrophoresis under reducing conditions, and the soluble TM antigen from the hydrogen peroxide-treat-ment cells was composed of five heterogeneous fragments of 80, 56, 33, 31 and 28 kDa. These compositions were quite similar to that observed for soluble TM fragments in human plasma. It is suggested that soluble TM antigen is not secreted from endothelial cells, but results from cellular damage.